Possibility of improving technological effectiveness of dairy wastewater treatment through application of active fillings and microwave rabiation - Zieliński, M.; Dębowski, M.; Krzemieniewski, M.; Brudniak, A.; Kisielewska, M. (Химия и технология воды, 2016)
The aim of the study was to determine the technological effectiveness of treatment process of model dairy wastewater in anaerobic reactors with active filling (AF), heated with electromagnetic microwave radiation (EMR). Experiments were conducted in a laboratory scale. The AF were produced using micro-pore extrusion technology. The study demonstrated that AF introduction to the technological system and application of EMR significantly improved the effectiveness of organic compounds, phosphorus removal and biogas production. Initial organic loading rate also affected the final results of wastewater treatment.